Playwriting a backstage guide - Rebellato, Dan 1968- (National theatre backstage guides, 2023)
"Drawing heavily on contemporary practice - where the conventional rules of playmaking are regularly turned inside-out - the book considers moments from a range of plays, with a focus on those from the National Theatre's 50-year repertoire. Crucially, it embraces the range of different dramaturgical structures and styles popular today and reflects the current openness of dramatic form. It celebrates the increasingly blurred boundaries between playwriting and devised work, focusing not just on individual dramaturgical choices, but also on collective collaborative processes. Therefore, much of the book's lessons about dramatic form are valuable for a devising company as much as for the solo author. The texts selected for discussion offer up a diverse range of choices for, in particular, female playwrights and writers of colour. Written in a style that's informal, inspiring and entertaining, this pithy but comprehensive resource is a book of tools, not rules, with its range of suggestions and provocations, exercises and tricks, examples and discussions"-- Provided by publisher.